Supporting multiple patient monitoring with head-worn displays and spearcons. (July 2019) - Klueber, Sara; Wolf, Erik; Grundgeiger, Tobias; Brecknell, Birgit; Mohamed, Ismail; Sanderson, Penelope
Abstract: In hospitals, clinicians often need to monitor several patients while performing other tasks. However, visual displays that show patients' vital signs are in fixed locations and auditory alarms intended to alert clinicians may be missed. Information such as spearcons (time-compressed speech earcons) that 'travels' with the clinician and is delivered by earpiece and/or head-worn displays (HWDs), might overcome these problems. In this study, non-clinicians monitored five simulated patients in three 10-min scenarios while performing a demanding tracking task. Monitoring accuracy was better for participants using spearcons and a HWD (88.7%) or a HWD alone (86.2%) than for participants using spearcons alone (74.1%). Participants using the spearcons and HWD (37.7%) performed the tracking task no differently from participants using spearcons alone (37.1%) but participants using the HWD alone performed worse overall (33.1%). The combination of both displays may be a suitable solution for monitoring multiple patients. Graphical abstract: Image 1 Highlights: Multiple-patient monitoring was tested with spearcons and head-worn displays. Monitoring accuracy was best with spearcons and head-worn display combined. Combined display may be suitable for monitoring multiple processes while multitasking.